Heart rate at first postdischarge visit and outcomes in patients with heart failure. Issue 13 (25th November 2017) - Kim, Tae-Hun; Kim, Hyungseop; Kim, In-Cheol; Yoon, Hyuck-Jun; Park, Hyoung-Seob; Cho, Yun-Kyeong; Nam, Chang-Wook; Han, Seongwook; Hur, Seung-Ho; Kim, Yoon-Nyun
Abstract : Objective: Heart rate control is important to prevent adverse outcomes in patients with heart failure (HF). However, postdischarge activity may worsen heart rate control, resulting in readmission. This study aimed to explore the implications of the heart rate differences between discharge and the first outpatient visit (D-O diff). Methods: We retrospectively identified 458 patients (male: 46%; mean age: 72 years) discharged after HF. The heart rates at admission, discharge and first outpatient visit were analysed. The primary outcome was a composite of cardiovascular (CV) death and readmission of non-fatal myocardial infarction (MI), non-fatal stroke or non-fatal HF over a mean follow-up of 16 months. Results: During follow-up, the clinical outcomes were noted in 223 patients (49%): HF, 199; stroke, 9; MI, 6; CV death, 9. The heart rate at the first outpatient visit (r=−0.311, P<0.001) and D-O diff (r=0.416, P<0.001) showed a better correlation with the time-to-clinical event than the heart rate at admission or discharge. The events group displayed a pronounced heart rate increase (13 beats/min) from discharge to the first outpatient visit compared with the event-free group (a decrease of 2 beats/min). A decrease less than −15 in the D-O diff showed a 4.5-fold risk of clinical outcomes during follow-up (P<0.001). Conclusions: A decreased D-O diff was related to the adverse outcomes of HF. The failure of heart rate control within more than 15 beats/min at the first outpatient visit was an independent factor for CV events.